Some Functional Sections in Topological Sequence Spaces. (9th July 2022) - Akdemir, Ahmet Ocak; Ersoy, Merve Temizer; Furkan, Hasan; Ragusa, Maria Alessandra
Abstract : Summability is a particularly fertile field for functional analysis application. Summability through functional analysis has become one of the most fascinating disciplines since it contains both interesting and challenging issues. In this paper, we aim to introduce four new sectional properties for topological sequence spaces: sectional weakly absolute convergence (WAC), sectional weak boundedness (WB), sectional weakly p -absolute convergence W p AC, and sectional weakly bounded variation (WBV). We have, also, investigate some of their relations and identities.